Pembuatan QR Code dan Membuat Identitas Toko,Serta Membuat Penetapan Harga Pokok, Studi Kasus: Toko Singgalang Ponsel - Nur Fitriana; Ahmad Riyadi; Nurul Indah Lestari; Aldika Putra Zega; Miftahul Jannah; Chikadetry Syalomita Siregar; Rizki Amelia; Sylvania Nadisah (LPPI UMN AL WASHLIYAH, 2025)
This article discusses how digital technology is applied at Singgalang Phone Store through a community service program. The goal of this program is to help Micro, Small, and Medium Enterprises (MSMEs) better understand and use digital technology to make their businesses more efficient. The activities include training on digital financial record-keeping, using QR Codes for payments, and marketing strategies that involve technology. The results show that digital technology helps speed up work and increase customer satisfaction. In conclusion, digital technology is very important for supporting the growth and sustainability of MSMEs.